Immersed Membrane Bioreactors for Produced Water Treatment - Brookes, Adam (Cranfield University, 2005)
The performance of a submerged membrane bioreactor for the duty of gas field produced water treatment was appraised. The system was operated under steady state conditions at a range of mixed liquor suspended solids (MLSS) concentrations and treatment and membrane performance examined. Organics removal (COD and TOC) display removal rates between 90 and 97%. Removal of specific target compounds Benzene, Toulene, Ethylbenzene and Xylene were removed to above 99% in liquid phase with loss to atmosphere between 0.3 and 1%. Comparison of fouling rates at a number of imposed fluxes has been made between long term filtration trials and short term tests using the flux step method. Produced water fed biomass displays a greater fouling propensity than municipal wastewater fed biomass from previous studies. Results indicate an exponential relationship between fouling rate and flux for both long and short term trials, although the value was an order of magnitude lower during long term tests. Moreover, operation during long term trials is characterised by a period of pseudo stable operation followed by a catastrophic rise in TMP at a given critical filtration time (tfi, ) during trials at 6 g. L"1. This time of stable operation, tfit, is characterised by a linear relationship between fouling rate and flux. Results have been compared with the literature. Data for membrane fouling prior to the end of t fit yielded a poor fit with a recently proposed model. Trends recorded at t> trlt revealed the fouling rate to follow no definable trend with flux. The system showed resilience to free oil shocking up to an oil concentration of 200ppmv. Following an increase in oil concentration to 500 ppmv, rapid and exponential fouling ensued.
Keywords: MBR.; Produced water; BTEX; oil; membrane fouling; sustainable flux